Taxpayers' Self-Efficacy And E-Tax System Adoption: The Moderating Role Of Business Location In South- West Nigeria - Mustapha, Bojuwon; Babatunde , Tijesu Daniel; Bamisaye, Theresa Omolade; Abiloro, Rafiyat Bosede; Lawal , Adenike Moronke (Universitas Indonesia Membangun (Inaba), 2025)
This study explored how taxpayers' self-efficacy relates to the adoption of e-tax systems, with a focus on the moderating role of business location in Southwest Nigeria. It aimed to determine the influence of taxpayers’ self-efficacy on e-tax adoption, examine its effect on business location, evaluate how location impacts e-tax adoption, and assess whether business location moderates the link between self-efficacy and e-tax adoption. A descriptive survey research design was employed, with a quantitative, deductive, and positivist approach. The study targeted all 23,289 registered SMEs in Southwest Nigeria, as reported by SMEDAN in 2023. A sample of 393 SMEs was selected using Taro Yamane’s formula and a multistage sampling technique. Data was analyzed using descriptive and inferential statistics, including logistic regression and the Sobel test. Findings revealed that taxpayers’ self-efficacy positively, though insignificantly, affects e-tax adoption (β = 0.32, p = 0.126). However, self-efficacy significantly influences business location (β = 0.78, p = 0.004), and business location significantly impacts e-tax adoption (β = 0.55, p = 0.011). Notably, business location significantly moderates the relationship between self-efficacy and e-tax adoption (moderating effect = 3.66, p = 0.0021). The study concludes that business location plays a crucial moderating role. It recommends that tax authorities (FIRS and SIRS) conduct regular training to enhance taxpayers’ digital competence and confidence.